A fuzzy AHP approach to evaluating differences between ocean container carriers and their customers. (19th March 2021) - Ergin, Ayfer
The study has investigated ocean container carrier selection criteria in order to determine the differences and similarities between carriers and their customers in the Turkish market. In application, four separate groups have used: carriers, freight forwarders, shippers, and consignees. For the first time, differences in perspective between carriers and their customers are studied in Turkey, eliminating the gap in knowledge about this market. It is also the first study to utilise fuzzy analytical hierarchy process (AHP) method to examine the differences in perceptions between ocean container carriers, freight forwarders, shippers, and consignees. This study contributes to the literature by employing both a new region and an unused method. The study's findings are that the most important sub-criterion for carriers and freight forwarders was low freight; meanwhile, the most important criterion for shippers was determined to be equipment availability. The most important sub-criterion of consignees was on-time notification of the customer.